2014
DOI: 10.4236/ijcm.2014.512094
|View full text |Cite
|
Sign up to set email alerts
|

Thoraco-Lumbar Junction Disc Herniation and Tight Filum: A Unique Combination?

Abstract: Purpose: The incidence of both symptomatic thoraco-lumbar junction disc herniation (TLJDH) and tight filum (TF) may be underestimated. Both conditions have a complex clinical presentation that may involve the distal spinal cord, conus medullaris, and/or cauda equina, including upper and/or lower motor neuron impairment, sensory impairment, urological and sexual dysfunction. The coexistence of both conditions has not been previously reported and may be a diagnostic and therapeutic challenge. Methods: We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…A report of six cases with combined TFT/lumbar disc herniation [ 9 ] demonstrated that that filum resection was an effective treatment, similar to our observations in this case. However, no symptomatic case with combined TFT/thoracic disc herniation has been reported.…”
Section: Discussionsupporting
confidence: 90%
“…A report of six cases with combined TFT/lumbar disc herniation [ 9 ] demonstrated that that filum resection was an effective treatment, similar to our observations in this case. However, no symptomatic case with combined TFT/thoracic disc herniation has been reported.…”
Section: Discussionsupporting
confidence: 90%
“…We decided to start with an anterior transthoracic hemivertebrectomy from the convex (left) side. Using our experience with video-assisted thoracoscopic microdiscectomies [ 12 , 13 ], we performed an anterior thoracoscopic hemivertebrectomy and release of adjacent levels with motor evoked potential (MEP) monitoring support, followed by an open posterior redression and stabilization procedure four levels above and below 10 days later. She made a swift recovery and has been doing fine with a follow-up of 3 years to date.…”
Section: Case Seriesmentioning
confidence: 99%